Histamine Intolerance—The More We Know the Less We Know. A Review - Hrubisko, Martin (Nutrients, 2021)
The intake of food may be an initiator of adverse reactions. Food intolerance is an abnormal non-immunological response of the organism to the ingestion of food or its components in a dosage normally tolerated. Despite the fact that food intolerance is spread throughout the world, its diagnosing is still difficult. Histamine intolerance (HIT) is the term for that type of food intolerance which includes a set of undesirable reactions as a result of accumulated or ingested histamine. Manifestations may be caused by various pathophysiological mechanisms or a combination of them. The problem with a “diagnosis” of HIT is precisely the inconstancy and variety of the manifestations in the same individual following similar stimuli. The diagnosing of HIT therefore requires a complex time-demanding multidisciplinary approach, including the systematic elimination of disorders with a similar manifestation of symptoms. Among therapeutic approaches, the gold standard is a low-histamine diet. A good response to such a diet is considered to be confirmation of HIT. Alongside the dietary measures, DAO supplementation supporting the degradation of ingested histamine may be considered as subsidiary treatment for individuals with intestinal DAO deficiency. If antihistamines are indicated, the treatment should be conscious and time-limited, while 2nd or 3rd generation of H(1) antihistamines should take precedence.